2016
DOI: 10.1038/srep24709
|View full text |Cite
|
Sign up to set email alerts
|

Rho-kinase/myosin light chain kinase pathway plays a key role in the impairment of bile canaliculi dynamics induced by cholestatic drugs

Abstract: Intrahepatic cholestasis represents a frequent manifestation of drug-induced liver injury; however, the mechanisms underlying such injuries are poorly understood. In this study of human HepaRG and primary hepatocytes, we found that bile canaliculi (BC) underwent spontaneous contractions, which are essential for bile acid (BA) efflux and require alternations in myosin light chain (MLC2) phosphorylation/dephosphorylation. Short exposure to 6 cholestatic compounds revealed that BC constriction and dilation were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
75
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(81 citation statements)
references
References 43 publications
6
75
0
Order By: Relevance
“…Fasudil is a potent Rho-associated protein kinase (ROCK) inhibitor [8,9,10,11,12,13] and vasodilator and has been used for the treatment of cerebral vasospasm [9] and many other diseases, such as cancer [14,15], allergy [16] and inflammation [17,18]. The systematic administration of Fasudil was reported protecting mice from experimental autoimmune encephalomyelitis (EAE) and shifting macrophages from M1 to M2 [19].…”
Section: Introductionmentioning
confidence: 99%
“…Fasudil is a potent Rho-associated protein kinase (ROCK) inhibitor [8,9,10,11,12,13] and vasodilator and has been used for the treatment of cerebral vasospasm [9] and many other diseases, such as cancer [14,15], allergy [16] and inflammation [17,18]. The systematic administration of Fasudil was reported protecting mice from experimental autoimmune encephalomyelitis (EAE) and shifting macrophages from M1 to M2 [19].…”
Section: Introductionmentioning
confidence: 99%
“…As observed with several other cholestatic drugs (Sharanek et al, 2016), we found that DCF provoked early dilatation of bile canaliculi at lower concentrations than those causing cytotoxicity and these bile canaliculi deformations were associated with alterations of taurocholic acid clearance as well as of expression of influx and efflux bile acid transporters. Although TNF-α did not obviously alter these major DCF cholestatic effects when added prior to and/or simultaneously with the drug this did not exclude that this cytokine could modulate bile acids synthesis and/or secretion.…”
Section: Dcf Induced An Apoptotic Response In Both Differentiated Andmentioning
confidence: 52%
“…Downstream effects of these knockouts range from reduced phosphorylation of adenosine monophosphate-activated protein kinase (30) to disruption of tight-junctional proteins such as Claudin-1 and zona occludens 1 (31) to reduced Wnt signaling activity. (32) The cholestasisinducing drug fasudil inhibits Rho-associated protein kinase and causes dephosphorylation of myosin light chain 2, which leads to dilatation of bile canaliculi of cultured hepatocytes (33) through dysregulation of cortical actin dynamics. When diameters of bile canaliculi increase, vesicles are formed at the apical membrane and released into the cytoplasm, followed by a decrease in canalicular diameter.…”
Section: Adaptation Of the Canalicular Networkmentioning
confidence: 99%